Anisakidae nematodes in the blackfin goosefish, Lophius gastrophysus Miranda-Ribeiro, 1915 purchased in the State of Rio de Janeiro, Brazil - doi: 10.4025/actascibiolsci.v35i1.12185 - Knoff, Marcelo; São Clemente, Sergio Carmona; Fonseca, Michelle Cristie Gonçalves da; Felizardo, Nilza Nunes; Lima, Francisco Carlos de; Pinto, Roberto Magalhães; Gomes, Delir Corrêa (Acta Scientiarum. Biological Sciences, 2012)
The blackfin goosefish is included in a prized fish category, representing valuable fishery resource worldwide. The aim of this study was to identify the Anisakidae larvae parasitizing this fish species, considering the hygienic-sanitary and public health importance of these parasites infecting specimens of the blackfin goosefish, Lophius gastrophysus Miranda-Ribeiro, 1915 (Lophiidae), purchased from markets in the municipalities of Cabo Frio, Niterói, Duque de Caxias and Rio de Janeiro; parasitological indices and sites of infection are presented. From March 2000 to December 2005, 87 specimens of Lophius gastrophysus were investigated for helminths. Seventeen fish (19.5%) were parasitized with larvae of anisakid nematodes. Anisakis simplex, Hysterothylacium sp. and Raphidascaris sp. appeared with prevalence of 1.14, 12.6 and 12.6%, intensity and mean intensity of infection of 1, 2.81, 10.5 and mean abundance of 0.01, 0.35 and 1.33 respectively. The sites of infection were stomach, stomach and intestine serosas and abdominal cavity. This is the first record of Anisakis simplex, Hysterothylacium sp. and Raphidascaris sp. for this species of fish.